Pengenalan Aplikasi Pengecoran Logam Berbahan Dasar Sampah Kemasan Kaleng Untuk Pembuatan Produk Wajan Bagi Masyarakat Kota Kendari - Sudia, Budiman; Aminur; Sisworo, Raden Rinova; Balaka, Ridway; Yurnidarsyah, Citra; Sudarsono; Samhuddin; La Hasanudin (Indonesian Journal of Community Services, 2022)
One of the classic problems that are difficult to overcome in urban life is environmental problems where waste is not handled properly, especially inorganic waste. Currently, the largest contributor to waste after organic waste is inorganic waste in the form of canned waste. The use of aluminum as a packaging material is due to its being lightweight, easy to shape, and does not endanger human health. On that basis, its use as packaging is widespread which also triggers the forerunner of the waste problem in people's lives. Aluminum waste will be a source of income for the community if it is handled properly by involving waste processing technology in the form of recycling technology through metal smelting or casting. This service program aims to introduce metal casting applications made from canned waste into frying pan products for the community in Lepo-Lepo, Kendari City. The activity stages include: socializing the introduction of aluminum-based cans of packaging waste and the practice of smelting aluminum cans in a crucible furnace and pouring molten metal into molds. The implementation of this service activity can raise awareness of participants to be able to process waste, especially aluminum can packaging into frying pan products, and create new jobs to improve the welfare of the local community.